M. QURAISH SHIHAB'S THOUGHT ON WASATHIYYAH (RELIGIOUS MODERATION) AND THEIR RELEVANCE TO ISLAMIC EDUCATION - Imam Mashuri,; Kholilur Rahman (International Conference on Humanity Education and Society (ICHES), 2022)
ABSTRACTFollowers of the Islamic religion should obey and follow the rules of the holy book Al-Qur'an. Because by making the Qur'an as a religious reference, happiness in the world and the hereafter will be achieved. But all of that does not necessarily make someone go to extremes (gulluw) because they are reluctant to accept rationality or ijtihad. Be it in terms of worship, faith, or in social life. Therefore, religious moderation (wasathiyyah) is considered the right choice, because in understanding the teachings of Islam, it is not uncommon for extreme views to appear by some over-textualist groups or otherwise make rationality the main benchmark in carrying out religion from over-rationalists. Therefore, it is deemed necessary to have an in-depth study of wasathiyyah (religious moderation) as well as its relevance to Islamic religious education. This study aims to explain the meaning of wasathiyyah (religious moderation) from various sides, especially from the perspective of M. Quraish Shihab's thoughts and their relevance to Islamic religious education. This research itself uses a qualitative approach. In the process of collecting data using the documentary study method. The data analysis technique used content analysis (Content Analysis). As for the results of the study, it can be concluded that wasathiyyah (religious moderation) is the ability to make religious texts the initial foundation in religion but does not at all close the space for rationality and ijtihad to be able to coexist in understanding Islamic teachings. Furthermore, it also revealed that M. Quraish Shihab's thoughts were relevant to Islamic Religious Education, as evidenced by the existence of Islamic religious education materials that were in accordance with M. Quraish Shihab's concept of religious moderation.Keywords: Quraish Shihab, Religious Moderation, Islamic Religious Education